ESENSI UTANG DALAM KONSEP EKONOMI ISLAM - Aziz, Abdul; Ramdansyah, Ramdansyah (Universitas Islam Negeri Sunan Kudus, 2016)
Meeting the needs of life is something that must be done. To meet these needs is constrained because keterbatas money as a tool applicable in the transaction, for which one needs the help of others for the fulfillment of the terms muamalah called the debt. Debt is an obligation for someone to pay if the debt maturity has been up, even the debt shall be the duty of someone since he was alive until he dies. We often hear when the bodies would be buried, who often say is the debt that will be transferred to the heirs of the new corpses to be buried. Seeing this context debt is an important role for someone to pay it off.